2018
DOI: 10.1038/s41419-017-0243-9
|View full text |Cite
|
Sign up to set email alerts
|

KRAS induces lung tumorigenesis through microRNAs modulation

Abstract: Oncogenic KRAS induces tumor onset and development by modulating gene expression via different molecular mechanisms. MicroRNAs (miRNAs) are small non-coding RNAs that have been established as main players in tumorigenesis. By overexpressing wild type or mutant KRAS (KRASG12D) and using inducible human and mouse cell lines, we analyzed KRAS-regulated microRNAs in non-small-cell lung cancer (NSCLC). We show that miR-30c and miR-21 are significantly upregulated by both KRAS isoforms and induce drug resistance and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 59 publications
0
38
0
1
Order By: Relevance
“…Although alterations such as gene amplification, deletion, and translocation are common events in genomic regions hosting miRNAs and can influence their expression in cancer (66), direct regulation by oncogenes and tumor suppressors can also significantly influence miRNA expression levels (27)(28)(29)(30)(31). Previous studies have suggested upregulation and functional roles for miR21, miR450b-5p, and miR30c in response to oncogenic KRAS in cancer (14)(15)(16)(17). Here we used primary MEFs with conditional expression of oncogenic KRAS (36) to identify key dysregulated miRNAs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although alterations such as gene amplification, deletion, and translocation are common events in genomic regions hosting miRNAs and can influence their expression in cancer (66), direct regulation by oncogenes and tumor suppressors can also significantly influence miRNA expression levels (27)(28)(29)(30)(31). Previous studies have suggested upregulation and functional roles for miR21, miR450b-5p, and miR30c in response to oncogenic KRAS in cancer (14)(15)(16)(17). Here we used primary MEFs with conditional expression of oncogenic KRAS (36) to identify key dysregulated miRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative mechanism for regulation of gene expression is via microRNAs (miRNAs) (13). However, our understanding of the role of miRNAs functionally regulating the consequences of KRAS activation is still limited (14)(15)(16)(17). The study of miRNA function is an alternative strategy to yield molecular insights necessary for the development of novel therapies against KRAS-driven tumors.…”
Section: Introductionmentioning
confidence: 99%
“…The interplay between miRNA and ROS in cancer treatment response has been discussed in recent reviews [256,257]. Non-coding RNAs such as miR-21 and miR-30c have shown upregulation with KRAS G12D overexpression, which as a result enhance regulation of Ras downstream pathways [207]. In contrast, a negative regulator of Ras includes the let-7 family which acts as a tumor suppressive miRNA and inhibits downstream signaling [104].…”
Section: Ras/raf/mek/erk (Mapk)mentioning
confidence: 99%
“…Zhu et al revealed that hsa-miR-182 downregulated RASA1 to suppress proliferation of lung squamous cell carcinoma through tissue microarray and quantitative PCR ( 60 ). Recently, Shi et al demonstrated that miR-30c and miR-21 were significantly upregulated by two KRAS isoforms in small-cell lung cancer and induced drug resistance by inhibiting key tumour suppressor genes such as neurofibromatosis type one (NF1), RASA1, BID, and RASSF8 ( 61 ). Mutations of EGFR result in drug resistance and relapse in patients with non-small cell lung cancer (NSCLC) ( 62 ).…”
Section: Rasa1 and Cancersmentioning
confidence: 99%